Confluence of suicide and drug overdose epidemics in young Australian males: common causality? - Richard Taylor; Andrew Page; Alex Wodak; Michael Dudley; Sonali Munot; Stephen Morrell (BMC, 2018)
Abstract Background Young adult (aged 20-34) males experience higher mortality than females, and in age groups immediately younger and older, and with considerable variation in death rates over time. Trends in mortality and the cause structure of deaths among young adult Australian males over 1979-2011 are investigated, with a focus on suicide and drug overdose. Methods Mortality data by age for the period 1979 to 2011 and Australian population figures were obtained from the Australian Bureau of Statistics (ABS). Cause of death was investigated using relevant International Classification of Diseases (ICD) codes, and mortality by cause was examined graphically over time according to various ICD aggregations. Mortality trends were contextualised in relation to labour market changes occurring in Australia from the 1980s to early 2000s. Results Although motor vehicle accident (MVA) mortality declined by half between 1980 and 1998 in males, this did not translate into a reduction in total young male mortality because of simultaneous increases in suicide, and drug-related deaths classified as either poisoning (external cause) or drug dependence (mental disorders). When both suicide and drug-related deaths declined concurrently after 1998, total 20-34 year male mortality declined by almost half (46%) over 1998-2011. Declines in external cause mortality accounted for 63% of the total mortality decline in 20-34 year males over 1998-2011. The close temporal coincidence (statistically significant) of increases and declines in suicide and drug-related deaths over a decade suggests related causality. Conclusions The coincidence of young male suicide and drug overdose mortality epidemics over the study period (excess deaths: 5000) suggest related causality such as exposure to common factors, including the labour market liberalisation and de-regulation of the 1990s, and deserves further investigation.